Pengaruh Ketepatan Waktu Penerbangan (On Time Performance) terhadap Kepuasan Penumpang Maskapai Malaysia Airlines di Bandar Udara Internasional Juanda Surabaya - Khairunnisa, Nadilla; Ginusti, Gallis Nawang (Jurnal Ground Handling, 2025)
ABSTRACT Flight punctuality is an important indicator in assessing the quality of an airline’s service. Flight punctuality reflects operational efficiency and has a direct impact on passenger satisfaction levels. This study aims to determine how much influence flight punctuality has on passenger satisfaction of Malaysia Airlines at Juanda International Airport Surabaya. This study uses a quantitative method approach. Data collection techniques are carried out by distributing questionnaires to a number of respondents selected using random sampling techniques. The data collected were analyzed using simple linear regression, partial test (t) and coefficient of determination. Based on the results of the partial test (t), the calculated t value > t table is 11,166 > 1,984 so that H0 is rejected and Ha is accepted. This shows that there is a significant influence between flight punctuality (X) and passenger satisfaction (Y). in addition, the results of the determination coefficient test show an R square (R2) value of 0,560, which means that flight punctuality has a 56.0% effect on passenger satisfaction, while the remaining 44.0% is influenced by other factors outside flight punctuality. Keywords: Flight punctuality, Passenger satisfaction, Malaysia Airlines